Influence of Limited or Completed Food Ingredients Shortage on the Longevity of Mediterranean Fruit Fly, Ceratitits capitata Wiedemann (Diptera: Tephritidae) - Asid Alanazi, Naimah (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2023)
One of the greatest harmful fruit pests is the Mediterranean fruit fly Ceratitis capitata (Wiedemann) (Diptera: Tephritidae). To study the feeding habits and how long the Mediterranean fruit fly, C. capitata can withstand the deficiency of a few food ingredients (water - sugar - protein), three laboratory experiments were executed. The first test; continuous feeding (through the live adults). The second test; 24 hours feeding for just emerged flies. The third test; 24 hours feeding for 24 hours - age flies. Each experiment consisted of the following formulations: Protein, sugar, water, sugar plus water, water plus protein, 10% sugar solution, and 5% buminal protein solution. Also, two control diet regimes were included in which they were total starvation and a typical adult fly meal of water and a mixture of (4 sugar: 1 protein). According to the findings, sugar was the most important dietary component, and its absence resulted in a clearly shorter fly life span across the three feeding groups. In contrast to sugar-free formulations (75.2 hrs.), which come in second place in terms of adult life span, water-based formulations (either alone (80 hrs.) or combined with protein (140.8 hours) or sugar (240 hours) or protein (alone (64.6 hours), in mixture with other components, or even as a 10% solution (240 hrs.)) all contributed to the adult fly’s superior longevity. Also, flies can exist starved in for three successive days without any sort of food. Overall, removing any sort of food from the area under interest, specially, materials that contains sugar or any sort of carbohydrates such as fruit residues, fallen ripen fruits as well as controlling honeydew producing insects is recommended to control the fruit fly.